Second hankel determinant for a subclass of analytic functions involving Q-analogue of Ruscheweyh operator - Suhila Elhaddad; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2020)
Let S be the class of analytic functions which are univalent and normalised in the open unit disc :1 <.Uzz Second Hankel determinant of 2243aaa for a class of analytic functions involving q-analoque of Ruscheweyh operator is given.